Gelation Kinetics, Melting and Foaming Characteristics of Turkey (Meleagris gallopavo) Skin Gelatin: Influence of Conventional Oven/Spray/Freeze-Drying Methods - Ozcan, Yilmaz; Kurt, Abdullah; Toker, Omer Said (WILEY, 2025)
This study was carried out to determine the influence of conventional oven drying (CDG), spray drying (SDG), and freeze drying (FDG) on the physicochemical, powder, functional, and gelling properties of turkey skin gelatin. SDG (12%) and FDG (13%) have lower yields than CDG (15%). SDG and FDG also had lower bulk density but higher Hausner ratio and Carr index values compared to CDG. However, spray and freeze-drying increased the expansion and stability of the gelatin foam, which also exhibited improved solution clarity and lightness compared to CDG. FDG (370.86 g) and SDG (365.02 g) had higher bloom strength values than CDG (321.55 g). The gelation temperatures of 23.8, 27.79, and 25.23 degrees C and the melting temperatures of 29.55, 32.79, and 30.84 degrees C were determined for CDG, SDG, and FDG, respectively. These results indicated that the temperature-dependent gel network formation tendency and melting resistance of SDG and FDG were enhanced, possibly due to their higher high molecular weight peptide fractions. Consistently, SDG and FDG had higher gelation kinetics (kgel) than CDG. The effect of the short time of spray drying and the low temperature of lyophilization on the formation of a less degraded protein structure compared to CDG was confirmed by SDS-PAGE and FTIR. The spray and freeze-drying methods may be suitable for the production of turkey skin gelatin for techno-functionally enhanced food and pharmaceutical applications.Practical Applications This research has potential applications in the food industry, primarily to demonstrate turkey skin gelatin as an alternative to bovine gelatin and that superior functional properties can be achieved under freeze-drying conditions.
Keywords: FUNCTIONAL-PROPERTIES; GOAT SKIN; EXTRACTION; CHALLENGES; CALCARIFER; Food Science & Technology